2018
DOI: 10.1093/jxb/erx459
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of the fuzzless seed trait in Gossypium barbadense

Abstract: Five genetic loci were found to be associated with the fuzzless seed trait in Gossypium barbadense, one of them containing MYB25-like_Dt, the best candidate for the N2 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 50 publications
2
72
2
Order By: Relevance
“…Long lint fibers (>10 mm) can be easily separated from seeds through the ginning process. Recent studies indicated that both lint and fuzz fibers may share common developmental pathways at least in early differentiation, despite being under different genetic controls (Turley and Kloth, 2002;Wan et al, 2014Wan et al, , 2016Wu et al, 2018;Zhu et al, 2018). Fuzz fibers initiate ?3 to 5 DPA (Stewart, 1975;Wan et al, 2016) and stop elongating ?10 DPA.…”
Section: Unraveling Cotton Fiber Development Using Fiber Mutants In Tmentioning
confidence: 99%
See 4 more Smart Citations
“…Long lint fibers (>10 mm) can be easily separated from seeds through the ginning process. Recent studies indicated that both lint and fuzz fibers may share common developmental pathways at least in early differentiation, despite being under different genetic controls (Turley and Kloth, 2002;Wan et al, 2014Wan et al, , 2016Wu et al, 2018;Zhu et al, 2018). Fuzz fibers initiate ?3 to 5 DPA (Stewart, 1975;Wan et al, 2016) and stop elongating ?10 DPA.…”
Section: Unraveling Cotton Fiber Development Using Fiber Mutants In Tmentioning
confidence: 99%
“…Fuzz fibers are usually <5 mm in length and remain attached to the seeds after ginning (Zhang et al, 2007;Mauney, 2015). Currently, numerous naturally occurring cotton fiber mutants have been identified globally and characterized at the genetic, gene expression, and, more recently, genetic mapping (map-based cloning) levels (Rong et al, 2005;Hinchliffe et al, 2011;Kim et al, 2013a;Wang et al, 2014a;Naoumkina et al, 2015;Hu et al, 2016;Wan et al, 2016;Thyssen et al, 2017;Zhu et al, 2018). It is worth noting that it is difficult and often unpractical to differentiate fuzz fibers from extremely short (<6 mm) lint fibers before or after ginning.…”
Section: Unraveling Cotton Fiber Development Using Fiber Mutants In Tmentioning
confidence: 99%
See 3 more Smart Citations